Az első világháború előtti katolikus nagygyűlések és a katolikus egyetem ügye Magyarországon - Csibi, Norbert (Per Aspera ad Astra, 2015)
During the 18th–19th centuries major universities in Europe significantly changed, and came under the influence of nation states. The Catholic Church, which always had an important role in the European scientific world, and established and maintained several Universities, had to answer a number of questions related to this fact. It was also important for her since the scientific-technical progress had a side effect which made more and more intellectuals turn away from religion. Nevertheless, this social group was exactly the key to perform a catholic reform. From the turn of the 19th and the 20th centuries, following the paradigm of foreign examples, congresses organized by the Catholics became regular in Hungary. After the sporadic and regional events of the 1890s, from 1900 these musters of the catholic public life were organized in the capital. The questions of public education – beside other religious and social issues – were always important parts in the agenda of these 2–3-day long events. The plans related to the foundation of a new Catholic University in Hungary were important issues of this topic before the First World War. In my paper I show the main proposals of these Hungarian plans in relations to the respective Vatican guidelines as well as to the foreign paradigms.